Zeolite-amended backfills for enhanced metals containment via soil-bentonite vertical cutoff walls - Hong, Catherine SooJung, author; Shackelford, Charles D., advisor; Bareither, Christopher A., committee member; Malusis, Mike A., committee member; Sale, Thomas C., committee member; Stromberger, Mary E., committee member (Colorado State University. Libraries, 2016)
Low hydraulic conductivity (k), soil-bentonite (SB) vertical cutoff walls are commonly used to contain contaminated groundwater in geoenvironmental applications. The low k of the SB cutoff walls is attributed, in part, to the high swelling property of the bentonite component of the backfill. In addition, the high cation exchange capacity (CEC) of the bentonite, typically on the order of 80 to 150 cmolc/kg, imparts some intrinsic attenuation capacity to the backfill for cations (e.g., metals) via cation exchange. However, due to the low amounts of bentonite in typical SB cutoff walls (i.e., < 10 % by dry weight), this attenuation capacity is limited in traditional SB cutoff walls. Therefore, consideration has been given to amending SB backfills with zeolites to enhance the attenuation or adsorption capacity. Zeolites are naturally occurring aluminosilicates with high CEC (180 to 400 cmolc/kg) and a cage-like structure that allow the zeolites to perform as a molecular sieve and as adsorbents for ammonium, heavy metals, cations, and radioactive wastewater. In this study, three types of zeolites (two types of chabazite and a clinoptilolite) were used as amendments for SB backfills to enhance the adsorption capacity with respect to two metals, viz., potassium (K) and zinc (Zn). The results of measurements of the slump, consolidation behavior, and k of the unamended and zeolite-amended SB backfills with ≤ 10 % zeolite (by dry weight) confirmed that the zeolite-amended SB backfills exhibited similar physical properties compared to those for the unamended SB backfill, including the low k (≤ 1.0×10-9 m/s) typically required for SB vertical cutoff walls. The results of batch equilibrium adsorption tests (BEATs) indicated that the added zeolite increased the adsorption capacity of the SB backfill, but the effectiveness differed for different types of zeolite and the different metals (i.e., K and Zn). The results of numerical simulations for transport of K and Zn through a hypothetical 1-m thick model cutoff wall based on the results of the BEATs indicated that the barrier containment durations increased relative to that for the unamended SB backfill by as much as 108 yr and 228 yr for backfills with 5 and 10 % zeolite amendment, respectively. Finally, the results of long-term column tests (1.05 to 3.75 yr) indicated that the retardation factor (Rd) for K with the 5 % zeolite-amended SB backfills was 2.4 to 3.2 times greater than that for the unamended SB backfill, whereas Rd for Zn was 1.4 to 2.2 times greater than that for the unamended SB backfill. Based on the results of this study, the addition of small amounts of zeolite (≤ 10 % by dry weight) to traditional SB backfills can significantly enhance the adsorption capacity of the SB backfills for metals, thereby enhancing the containment performance of vertical cutoff walls comprising zeolite-amended SB backfills. However, the magnitude of any enhanced containment is dependent on both the adsorption capacity and the adsorption behavior of the specific metal with the specific backfill, and will be dependent on both the type and amount of the added zeolite.
Keywords: bentonite; soil-bentonite backfill; zeolite; metals; adsorption; vertical cutoff wall